Solid-state photocrosslinking of hyaluronan microfibres - Bobula, Tomáš; Běťák, Jiří; Buffa, Radovan; Moravcová, Martina; Klein, Pavel; Židek, Ondřej; Chadimová, Veronika; Pospíšil, Robert; Velebný, Vladimír (Carbohydrate polymers, 2015)
Hyaluronan (HA) was chemically modified to a photocurable derivative by the acylation with a mixed anhydride of trans-cinnamic acid and characterized by UV, IR and 2D NMR spectroscopy. Photocurable HA was processed to a microfibrous structure by wet-spinning technology. Water solubility of otherwise water-soluble HA microfibres was reduced significantly by the solid-state photocrosslinking. We also investigated that the nature of polymer structure had a great impact to a final crosslink ratio. The analysis of the mechanical properties showed higher ultimate tensile strength and increased rigidity of the photocrosslinked fibres in comparison to the untreated ones. Moreover all tested materials are regarded as biocompatible according to the tests of cell viability, phototoxicity and enzymatic degradability, which make them suitable candidates for numerous biomedical applications.
Keywords: Hyaluronic Acid; myši; Ultraviolet Rays; rozpustnost; Photocrosslinking; Fibroblasts; Tensile Strength; fibroblasty; Cinnamic acid; 3T3 Cells; buňky 3T3; kyselina hyaluronová; reagencia zkříženě vázaná; Cross-Linking Reagents; Hyaluronan; Animals; Mice; zvířata; Trans-cinnamic acid (CID 444539); ultrafialové záření; Solubility; Wet-spinning; pevnost v tahu; Viscosity; Fibres; Hyaluronan (CID 3084049); viskozita; Crystallization; krystalizace